CCL7 promotes macrophage polarization and synovitis to exacerbate rheumatoid arthritis - Jun Chen; Shuo Shi; Xiaojia Li; Feng Gao; Xu Zhu; Ru Feng; Ke Hu; Yicheng Li; Shuiyuan Chen; Rongkai Zhang; Xiaoshuai Wang; Changhai Ding; et al. (iScience)
Summary: Chemokine C-C motif ligand 7 (CCL7) is implicated in various immune and inflammatory processes; however, its role in rheumatoid arthritis (RA) remains unclear. In this study, we observed that CCL7 expression was upregulated in synovial M1-polarized macrophages and in the serum of RA mice and patients. CCL7 was found to promote macrophage polarization toward the M1 phenotype while inhibiting M2 differentiation in vitro. Furthermore, intra-articular injection of recombinant CCL7 protein in mice resulted in enhanced M1 polarization, increased inflammation, and fibrosis within synovial tissues, which exacerbated arthritis-associated pain. These effects were partially mitigated by treatment with a CCL7 neutralizing antibody. Mechanistically, we identified a CCL7 autocrine positive feedback loop that amplifies inflammation via the CCL7-CCR1-JAK2/STAT1 pathway. Collectively, our findings reveal a previously unrecognized CCL7-mediated autocrine inflammatory amplification loop that modulates macrophage polarization and exacerbates RA progression, positioning CCL7 as a potential therapeutic target for RA.